Water and fluid intake in the prevention and treatment of functional constipation in children and adolescents: is there evidence?, - Sabine Nunes Boilesen; Soraia Tahan; Francine Canova Dias; Lígia Cristina Fonseca Lahoz Melli; Mauro Batista de Morais
Abstract Objective: To study the evidence on the role of water and fluid intake in the prevention and treatment of functional intestinal constipation in children and adolescents. Source of data: A search was carried out in the Medline database (between 1966 and 2016) for all published articles containing the following words: constipation, water, and fluids, published in Portuguese, English, and Spanish. All original articles that assessed children and adolescents were selected by title and abstract. The references of these articles were also evaluated. Synthesis of data: A total of 1040 articles were retrieved. Of these, 24 were selected for reading. The study included 11 articles that assessed children and adolescents. The articles were divided into two categories, those that evaluated water and fluid intake as a risk factor for intestinal constipation and those that evaluated their role in the treatment of intestinal constipation. Five articles were included in the first category. The criteria for assessing fluid intake and bowel rhythm were different in each study. Three studies demonstrated an association between low fluid intake and intestinal constipation. Regarding treatment, five articles with heterogeneous methodologies were found. None of them clearly identified the favorable role of fluid intake in the treatment of intestinal constipation. Conclusion: There are few articles on the association between fluid intake and intestinal constipation. Epidemiological evidence indicates an association between lower fluid intake and intestinal constipation. Further clinical trials and epidemiological studies that consider the international recommendations for fluid intake by children and adolescents are required.